A Clinical Case of Comorbid Adenocarcinoma of the Upper Lobe of the Left Lung and Chondroma of the Diaphragm - A. V. Bazhenov; R. B. Berdnikov; D. N. Pilkevich; I. Ya. Motus; A. S. Berdnikova; I. I. Badykov (Туберкулез и болезни лёгких)
The article describes a clinical case of comorbid peripheral lung cancer and extraskeletal chondroma of the diaphragm detected in the patient during chest computed tomography performed as a part of examination after renal colic. The X-ray signs of the masses were completely different, and those lesions were immediately identified as two different pathologies.